2019
DOI: 10.3389/fnbot.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Body Randomization Reduces the Sim-to-Real Gap for Compliant Quadruped Locomotion

Abstract: Designing controllers for compliant, underactuated robots is challenging and usually requires a learning procedure. Learning robotic control in simulated environments can speed up the process whilst lowering risk of physical damage. Since perfect simulations are unfeasible, several techniques are used to improve transfer to the real world. Here, we investigate the impact of randomizing body parameters during learning of CPG controllers in simulation. The controllers are evaluated on our physical quadruped robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, our investigations demonstrate the need for a mechanism of stability and gravity compensation to handle this task. Successful applications in robot locomotion using neural networks generally rely on position control either of stiff robots [33], [34], either of small and light compliant robot [15]. On a heavy torque-controlled compliant robot, in contrast, the lift-off cannot be easily guaranteed in the absence of a gravity compensation mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our investigations demonstrate the need for a mechanism of stability and gravity compensation to handle this task. Successful applications in robot locomotion using neural networks generally rely on position control either of stiff robots [33], [34], either of small and light compliant robot [15]. On a heavy torque-controlled compliant robot, in contrast, the lift-off cannot be easily guaranteed in the absence of a gravity compensation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the model could also handle disturbance and small obstacles by naturally generating recovery foot trajectories [13]. Pure reflex-based locomotion has also been achieved in robotics where embodied walking, trotting and bounding gaits were implemented on small compliant quadruped robots using only proprioceptive feedback with no timing information [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…The main contribution of the paper is investigating the advantages of using a learning control module during the optimization of the locomotion patterns for a quadruped robot rather than employ it when the optimal locomotion patterns have already been found (as it is usually done in already existing approaches, Urbain et al, 2018; Vandesompele et al, 2019). This idea comes from nature since evolution has always been acting on plastic and learning systems.…”
Section: Discussionmentioning
confidence: 99%
“…Robots might evolve to match the specificities of the simulation, which differ from the real-world constraints. To prevent this problem, many approaches can be possible, such as adding independent noise to the values of the sensors or changing the robot dynamic model and its interaction with the environment (Nolfi et al, 2000; Vandesompele et al, 2019). In comparison to the classical approach where this simulation variability is added during the evolutionary optimization, in this research, the possibility of overcoming the reality gap and the transferability of the approach is demonstrated afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…The continuation of this work has three main directions: improve the controller, incorporate visual information and integrate arm motion. To improve the controller, the network parameters can be pre-trained with domain randomization in simulation as in [39], [19] to fine tune the adaptive controller. To increase the performance of the controller the SNN can be executed with neuromorphic hardware such as SpiNNaker [40] or Loihi [41] to take advantage of the efficient real time execution of SNN [42].Neuromorphic hardware can also be used to directly use the spike activity of the network to control the motors [43] or by using event-based touch sensors [44] to further exploit the characteristics of SNN in terms of energy consumption and information processing [4].…”
Section: Parameters Finger Primitivesmentioning
confidence: 99%